The Migration-Development Nexus in Somaliland: Critical Voices from the Somali Diaspora - Fagioli-Ndlovu, Monica (African Human Mobility Review, 2021)
International development agencies have recently started to mobilise the Somali diaspora for state-building programmes. Somali diaspora experts and government officials are critical of state-building programmes run by UN agencies. By relaying critical voices from Somali diaspora experts involved in state-building programmes in Somaliland, this article looks at the emergence of the idea of migration for development. After reviewing recent critical works by transnational migration scholars, this article also draws on the work of African diaspora scholars. The latter have critiqued the mobilisation of the African diaspora as a way to serve only the Millenium Development’s Goals, yet failing to empower the African state (Clark, 2010; Zeleza, 2010). The article discusses how Somali diaspora experts are mobilised by international organisations in development and state-building programmes in Somaliland, and yet excluded from decision-making processes involved in those programmes. Despite the exclusion of Somali government officials and diaspora experts from the design of programmes run by UN agencies, the Somali diaspora and some local officials have been particularly active in creating the economic and political foundations that have enabled a re-emergence of the state in Somaliland and Somalia.